The cyclic nucleotide-gated channels CNGC2 and CNGC4 support systemic wound responses in Arabidopsis thaliana - Johns, Sarah; Wiegman, Erin; Bakshi, Arkadipta; Gilroy, Simon (Frontiers in Plant Science, 2025)
IntroductionThe local perception of a stimulus such as wounding can trigger plant-wide responses through the propagation of systemic signals including the vascular transport of diverse chemical messengers, the propagation of electrical changes, and even potentially hydraulic waves that rapidly spread throughout the plant body. These systemic signals trigger changes in second messengers such as Ca2+ that then play roles in triggering subsequent molecular responses. Although the glutamate receptor-like (GLR) channels GLR3.3 and GLR3.6 are known to be essential for the vascular propagation of wound-induced electrical and Ca2+ signals, additional channels and/or transporters are likely necessary to further spread responses across the plant. We hypothesized that members of the cyclic nucleotide-gated family of ion channels (CNGCs) might also be involved in the systemic component of this process.MethodsAn analysis of the systemic induction of defense genes was made using qPCR and patterns of Ca2+ signaling were monitored in plants expressing the GFP-based Ca2+ sensor GCaMP. Wild-type responses were compared to those seen from a library of CNGC mutants.ResultsOf all the CNGC family members tested, only mutants in CNGC2 and CNGC4 showed disruption in the patterns of both leaf-to-leaf and root-to-leaf wound-triggered systemic induction of defense gene expression. The mutants in these channels showed wild-type-like propagation of Ca2+ increases from the wound site but exhibited a limited spread of the Ca2+ wave from the vasculature to other tissues of distal leaves.DiscussionCNGC2 and CNGC4 likely play roles in spreading the Ca2+ signal through systemic leaves to help further propagate and amplify the plant-wide wound response. Although CNGC19 has previously been shown to be involved in Ca2+ signaling at the wound site, knockouts in this gene did not disrupt the long-distance element of the wound response. These findings suggest that the molecular machinery required to trigger the local reaction to damage is likely, at least in part, distinct from the activities that support the systemic spread of the response throughout the plant.